Optimization of the jaloe kayoh seat design using the quality function deployment (QFD) method based on anthropometric measurements of the Acehnese Society - Akram Tamlicha; Samsul Rizal; Iskandar Hasanuddin; M.M. Noor; Rahmad Ferdiansyah; Sri Rahmawati; Nazaruddin Nazaruddin (Jurnal POLIMESIN, 2023)
Jaloe Kayoh is a traditional canoe used by Aceh's fishing communities to catch fish in downstream rivers and shallow waters. The current Jaloe Kayoh design does not meet ergonomic aspects, especially in the user's seat position component. It is known from the results of distributing the Nordic Body Map (NBM) questionnaire at the initial stage of the study which was distributed to 30 respondents, that 9 out of 27 fisherman's body parts were in the "very high" complaint score. This complaint is also supported by data on the user's sitting position by bending the legs to form an angle of 70°, while the ideal sitting position is with the body upright and bending the legs at an angle of 90°-135°. Because this can lead to complaints that have an impact on the risk of long-term injury such as Musculoskeletal Disorders (MSDs) so this study aims to design a seat for Jaloe Kayoh users according to anthropometric measurements to avoid the risk of long-term injury. The design of the Jaloe Kayoh stand was carried out using the anthropometric approach of Acehnese fishermen and the Quality Function Deployment (QFD) method as a reference for researchers to determine the design according to the wishes of the user. The anthropometric dimensions used in this design are popliteal height (PH), buttock-popliteal length (BPL), hip breadth (HB), backrest height (BH), elbow rest height (ERH), and shoulder breadth (SB). Data Calculation from anthropometry produces the 5th, 50th and 95th percentile measurements, which will be used in designing the seat position for Jaloe Kayoh users. The three percentile values result in a new measure of the design; PH is 39.31 cm; BPL of 48.43 cm; HB is 40.31 cm; BH is 61.37 cm; ERH of 100o; SB is 52.26 cm. So based on the QFD method produced by the house of quality, it produces a design for the Jaloe Kayoh seat position that is in accordance with what the user wants